(untitled) (Journal Of Educational and Psychological Researches, 2012)
The research explores the shapes preferred by children and the extent to which it can be utilized on the experimental kindergarten at the Woman’s School of Education. To achieve the goal, the researcher has displayed pictures that have been chosen from within the research boundaries which represent four categories: Geometrical shapes which included (squares, rectangles, triangles, and circles), agricultural shapes which included (apples, oranges, bananas, and grapes), motion pictures shapes (cartoon characters) which included (Jerry the mouse, Twitty the bird, Bugs Bunny the rabbit, and Winnie the pooh), and animal shapes which included (dogs, fishes, frogs, and horses) to the sample children of (60) child (boys and girls) that have been randomly chosen from four different kindergartens from the city of Baghdad, with that an observation sheet of the shapes demonstrated was used with two fields (prefer, does not prefer) where the researcher recorded the children’s response. After eliminating redundancies and using the percentile method to draw statistics, the following results came out (from most preferred to least – per category): • Geometrical shapes are: rectangular, circle, square, triangle • Agricultural shapes: bananas, grapes, apples, oranges • Cartoon characters: Twitty the bird, Bugs Bunny the rabbit, Jerry the mouse, Winnie the pooh • Animal shapes: fish and horse shared 1st, dog, frog Then these results were checked against the furniture in the experimental kindergarten at the Women’s School of Education / Kindergarten Department and the results showed that most of these shapes were not utilized at the kindergarten even though it is a standardized kindergarten. Based on the results of the research, the researcher advised with recommendations to utilize the shapes most preferred by the kindergarten children in different ways that the children interact with them, for example: Furniture, toys, utensils, teaching tools, beddings, carpets, curtains, etc.